PERKAWINAN BEDA AGAMA DILIHAT DARI HUKUM POSITIF INDONESIA DAN ASAS ASAS HUKUM PERDATA INTERNASIONAL - Emerentia Nathawira; Mia Hadiati (Fakultas Hukum Universitas Tarumanagara, 2022)
The legality of interfaith marriages, particularly between Indonesian citizens and foreigners, is the focus of this investigation. With the assistance of statutes and regulations, this study adopts a normative legal approach. In simple terms, Indonesian marriage must adhere to Article 2 jo. UU No. 56, as amended by Section 1 of 1974, which governs marriage. The analysis reveals that interfaith marriages are in violation of international private law and Indonesian positive law, so they cannot be annulled. There are a lot of steps that need to be taken, whether in Indonesia or elsewhere, to end a marriage. In this way the local area should know how dangerous interfaith marriage is, despite the fact that it has a high gamble, the local area just ganders at it with one eye. whether or not the marriage is valid. It is possible that the number of interfaith marriages will be lower than the percentage scale for this year because of the government's important role in early counseling on the dangers of interfaith marriage. One way for people to learn how to choose a partner correctly and marry in accordance with religious law is through counseling.